The Effect of Aloe Vera Bioreagent as a Frother and Collector in the Gold Ore Flotation Process on Increasing Grade and Recovery - Aufa Asna; Azalia Songli; Rizka Nabilah; Syahwanul Ikhsan; M. Fajar Rickiadi; Tri Wahyuningsih (Journal of Metallurgical Engineering and Processing Technology, 2024)
One of the concentration processes in processing sulfide gold ore is the flotation technique which takes advantage of differences in mineral surface properties by adding chemical reagents. The addition of chemical reagents to the flotation process can cause environmental problems. Therefore, efforts are needed to replace chemical reagents with more environmentally friendly materials. In this research, an attempt was made to replace chemical reagents with a commonly found plant extract, namely aloe vera, as a bioreagent. Bioflotation experiments on a laboratory scale were carried out using a Denver flotation cell with an aloe vera reagent as a frother. This gold mineral bioflotation experiment was carried out on a 150 mesh size fraction. The results of increasing concentrate levels by flotation indicate that the aloe vera reagent as a frother is able to produce biosurfactants which replace chemical reagents as a more environmentally friendly biofrother and biocollector. This can be concluded based on flotation experiment data with bioreagent which has been tested showing an Au content value of 10.09 and a recovery of 96.15%, while flotation using chemical reagents shows an Au content value of 10.50 and a recovery of 95.96%. So the use of aloe vera as an environmentally friendly bioreagent in the flotation process releasing low sulfidation gold is more effective than the use of chemical reagents because it is indicated that there is a biosurfactant content in aloe vera.